Tumor-associated lymphatic vessel density is a reliable biomarker for prognosis of esophageal cancer after radical resection: a systemic review and meta-analysis - Li, Jin; Wang, Qing-Bo; Liang, Yu-Bo; Chen, Xing-Ming; Luo, Wan-Ling; Li, Yu-Kai; Chen, Xiong; Lu, Qi-Yu; Ke, Yang (Frontiers in Immunology, 2024)
Purpose: To explore whether tumor-associated lymphatic vessel density (LVD) could be a biomarker for the prognosis of patients with esophageal cancer after radical resection. Methods: A systematic literature search was performed through PubMed, EMBASE, Wanfang Data, and Cochrane Library from the inception of databases until March 19, 2024. The selected studies investigated overall survival (OS) and/or recurrence-free survival (RFS) of patients with esophageal cancer with different levels of LVD after radical resection. The OS and RFS data were pooled as hazard ratios (HR) and 95% confidential interval (CI). Furthermore, the standardized mean differences (SMDs) and 95% CI were aggregated to evaluate the correlation between LVD and clinicopathological features. Results: A total of 10 retrospective studies of 1,201 patients were finally included for the meta-analysis. Patients with esophageal cancer with a high level of LVD exhibited worse OS (HR 1.65, 95% CI 1.18 to 2.31) and RFS (HR 1.57, 95% CI 1.09 to 2.26) than those with a low level of LVD.Subgroup analysis of different pathological subtypes revealed that patients with esophageal adenocarcinoma with a high level of LVD had significantly worse RFS (HR 2.84, 95% CI 1.61 to 5.02) than those with a low level of LVD; while patients with esophageal squamous cell carcinoma with a high level of LVD had similar OS (HR 1.52, 95% CI 0.93 to 2.47) and RFS (HR 1.03, 95% CI 0.72 to 1.48) to those with a low level of LVD. Furthermore, tumors with lymph node metastasis had significantly higher levels of LVD than those without lymph node metastasis (SMD = 1.11, 95% CI 0.54 to 1.67). Tumors at the stages III-IV had significantly higher levels of LVD than those at the stages I-II (SMD = 1.62, 95% CI 0.90 to 2.A high level of LVD in tumor was associated with worse survival of patients with esophageal cancer after radical resection, especially in patients with esophageal adenocarcinoma. Tumor-associated LVD is a new parameter that should be measured in postoperative pathology for predicting the prognosis of patients with esophageal cancer.Systematic review registration: PROSPERO (https://www.crd.york.ac.uk/prospero/) identifier CRD42024553766.